TFSR: trust factors evaluation-based secure routing protocol for wireless sensor network. (2015) - Geetha, V.; Chandrasekaran, K.
Wireless sensor network (WSN) is an emerging technology, with tiny nodes to sense the data and collect it at sink node. The cryptographic techniques are not sufficient to ensure the security against blackhole, sink hole, DoS attacks, etc, as the nodes are deployed in open environment. Our main goal is to develop a trust-based secure communication system for WSN at network layer. We have identified various trust factors and developed a trust model for each trust factor to ensure security. We have proposed and analysed our trust factors evaluation-based secure routing (TFSR) protocol using network simulator NS2. The result shows that trust factors and trust models enhances secure communication in WSN for various possible attacks. The proposed model shows 96% of improvement, when alternative path for communication is available in the network. The result also shows total improvement of 30% to 35% in case of large networks.